2007
DOI: 10.1007/s00442-007-0920-y
|View full text |Cite
|
Sign up to set email alerts
|

Leaf litter input mediates tadpole performance across forest canopy treatments

Abstract: Understanding the mechanisms limiting the distributions of organisms is necessary for predicting changes in community composition along habitat gradients. In many areas of the USA, land originally cleared for agriculture has been undergoing a process of reforestation, creating a gradient of canopy cover. For small temporary wetlands, this gradient can alter abiotic conditions and influence the resource base of wetland food webs by affecting litter inputs. As distributions of amphibians and many other temporary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
68
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(79 citation statements)
references
References 48 publications
9
68
1
1
Order By: Relevance
“…The extent of canopy cover over breeding ponds and the amount and composition of leaf litter in pond basins are factors that play a strong role in the distribution and abundance of some species of amphibians. The presence of canopy and composition of leaf litter and detritus may influence primary productivity, nutrient cycling, hypoxia and, consequently, larval development (Skelly et al 2002;Halverson et al 2003;Rubbo and Kiesecker 2004;Mokany et al 2008;Williams et al 2008;Sacerdote and King 2009;Maerz et al 2010;Stephens et al 2013). For example, in Michigan, litter from Green Ash -a tree species often planted at WRP sites in our study -significantly increased growth, development and survival of larval Wood Frogs (Lithobates sylvaticus), compared to litter composed of other tree species (Stephens et al 2013).…”
Section: Amphibian Occurrence At Restored Versus Natural Forested Wetmentioning
confidence: 74%
“…The extent of canopy cover over breeding ponds and the amount and composition of leaf litter in pond basins are factors that play a strong role in the distribution and abundance of some species of amphibians. The presence of canopy and composition of leaf litter and detritus may influence primary productivity, nutrient cycling, hypoxia and, consequently, larval development (Skelly et al 2002;Halverson et al 2003;Rubbo and Kiesecker 2004;Mokany et al 2008;Williams et al 2008;Sacerdote and King 2009;Maerz et al 2010;Stephens et al 2013). For example, in Michigan, litter from Green Ash -a tree species often planted at WRP sites in our study -significantly increased growth, development and survival of larval Wood Frogs (Lithobates sylvaticus), compared to litter composed of other tree species (Stephens et al 2013).…”
Section: Amphibian Occurrence At Restored Versus Natural Forested Wetmentioning
confidence: 74%
“…Overall, little is known about how leaf litter inputs affect invertebrate communities in ephemeral wetlands and some studies have documented differential effects (Magnusson and Williams 2006;Batzer and Palik 2007). For amphibian larvae, Williams et al (2008) found that shifting from grassdominated litter to hardwood tree litter negatively impacted amphibian success, likely because of decreased phytoplankton growth rates. Further, large amounts of organic matter can decrease DO levels during decomposition (Magnusson and Williams 2006).…”
Section: Discussionmentioning
confidence: 96%
“…Canopy openings and shifts in species composition of vegetation can alter microclimatic factors such as the duration and intensity of light, levels of temperature and moisture, as well as the accumulation, quality and decomposition of leaf litter [111]. In turn, the extent of canopy cover over wetlands [112][113][114] and the composition of leaf litter in the pond basin [115,116] may play a strong role in the reproductive success of some aquatic-breeding amphibians.…”
Section: Habitat Changementioning
confidence: 99%